ANALYSIS OF FACTORS AFFECTING THE DEVELOPMENT OF COMMUNITY TOURISM SERVICES IN HA GIANG PROVINCE - Nguyen Thu Thuy Thuy; Nguyen Quang Hop (International Journal of Business and Social Science Research, 2021)
With 450 questionnaires, the authors used SPSS software to analyze and found that the researched factors all had a positive impact on the development of community tourism services in Ha Giang province. In particular, the degree of influence on the development of CBT services in Ha Giang province in the order of importance is as follows: The level of organization and management of the tourism industry (QL), The participation of the community in the development of community tourism (TG), Tourism Resources (TN), Infrastructure Development (HT), Human Resource Training Development (NL). This result is the basis for us to choose appropriate solutions to improve the quality of community tourism services in Ha Giang province in the future.